Cryptic diversity in the Azorean beetle genus Tarphius Erichson, 1845 (Coleoptera: Zopheridae): An integrative taxonomic approach with description of four new species - Borges, Paulo A. V.; Amorim, Isabel R.; Terzopoulou, Sofia; Rigal, François; Emerson, Brent C.; Serrano, Artur R.m. (Zootaxa, 2017)
Recent findings based on molecular data support the occurrence in the Azores of several independently evolving lineages of the beetle genus Tarphius Erichson, 1845 (Coleoptera: Zopheridae Solier, 1834) and higher species richness masked by cryptic diversity, needing formal taxonomic description. All Tarphius from the Azores are revised using an integrative taxonomic approach, using evidence from morphology, morphometrics and molecular data to delimit species. Our results reveal that Azorean Tarphius comprise at least five phyletic lineages, two of which share a similar morphology, despite being divergent at the molecular level. A total of four new species are described grouped into two complexes: i) two new species in the “complex tornvalli” with the new taxa Tarphius relictus sp. nov. (Terceira) and Tarphius furtadoi sp. nov. (São Jorge, Faial and Pico) and; ii) two new species in the “complex azoricus-wollastoni-depressus” with the new taxa Tarphius gabrielae sp. nov. (Pico) and Tarphius floresensis sp. nov. (Flores). Descriptions, photographs of holotypes and morphological details, and remarks on diagnostic features comparing similar species are presented. Additional information on the distribution and conservation status of the 12 described species in the archipelago is also provided.